Screening for Lung Cancer - McWilliams, A.; Brims, Fraser (Elsevier, 2017)
Preceded by: The IASLC multidisciplinary approach to thoracic oncology / executive editor, Harvey I. Pass; editors: David Ball, Giorgio V. Scagliotti. [2014]